Dampak Latihan Resistance Band Terhadap Peningkatan Teknik Passing Kaki Bagian Dalam Pada Siswa Ekstrakurikuler Futsal SMP Negeri 2 Colomadu - Ageng Nugroho Aji; Eko Sudarmanto; Anugrah Nur Warthadi; Gatot Jariono (Ilmu Olahraga, 2026)
This study aims to examine the effect of resistance band training on improving inner leg passing skills in futsal extracurricular students of SMP Negeri 2 Colomadu. The study used a quantitative approach with a pseudo-experimental design (one group pretest-posttest). The research sample amounted to 17 students who were selected through purposive sampling techniques based on the criteria of activeness and physical condition. The instrument used was a 30-second passing-control test to measure the accuracy and consistency of the pass. Treatment in the form of a resistance band training program is given for 6 weeks with a frequency of 3 times per week. Data analysis was carried out using normality tests, hypothesis tests, homogeneity tests, and paired sample t-tests, with the help of the SPSS program. The results showed an increase in the average score from 7.24 in the pre-test to 11.35 in the post-test, with a difference of 4.11 points. The results of the hypothesis test showed a significant difference (p < 0.05). Which means there is a significant difference between before and after treatment. These findings suggest that resistance band training has a positive influence on improving muscle strength, stability, and coordination of motion which contributes directly to passing quality. Thus, this training method is effectively used as an alternative in improving basic futsal technique skills in students.